Comparative Analysis of the Dissemination Effects of E-Cigarette Regulation on China’s Douyin Platform and the Overseas Version of the Tiktok Platform - Yuzhi CHENG; De CHEN; Yafei HU; WANG, Juanjuan; Zhengyang GONG; Hengwei DAI (The Journal of Medicine, Humanity and Media, 2025)
Objective: This study aims to compare the content strategies of Douyin and TikTok regarding e-cigarette regulation videos, exploring how each platform adapts to its respective audience. Methods: This study employs quantitative and qualitative methodologies to analyze e-cigarette regulation content on Douyin and TikTok. Data collection involved scraping videos using specific keywords related to e-cigarette regulations. We gathered 300 videos from each platform, with data collected over a six-month period from January 2020 to March 2024. For data analysis, we used frequency distribution to identify the prevalence of various elements such as video sources and emotional attitudes. Multidimensional Scaling (MDS) was applied to assess thematic frameworks and visually explore how different themes cluster across platforms. Finally, the Independent Samples T-Test was utilized to compare audience interactions, specifically likes, shares, and comments, between Douyin and TikTok. These methods provide a comprehensive view of how e-cigarette regulation is portrayed across different cultural contexts and how audiences engage with this content. Results: The findings indicate that TikTok tends to engage a global audience with diverse thematic content and higher interaction rates, particularly in sharing. Douyin, meanwhile, focuses on detailed policy discussions relevant to its Chinese audience, aligning with local regulatory concerns. Differences in thematic framing and audience interaction between the platforms were statistically significant, while similarities in emotional attitudes and some video sources suggest universal strategies across platforms. Conclusion: The distinct content strategies on Douyin and TikTok reflect their adaptation to different cultural and regulatory environments. This study highlights the importance of platform-specific strategies in engaging with local versus global audiences and offers insights into effective digital communication in varied regulatory landscapes.